Hubungan antara Penguasaan Literasi Digital dan Pemanfaatan AI dengan Kinerja Karyawan di Industri Ekonomi - Mujtahidin, Mujtahidin; Zulkifli, Zulkifli; Hudaeri, Hudaeri (Primary Journal of Multidisciplinary Research, 2025)
This study aims to examine the relationship between digital literacy proficiency and the utilization of artificial intelligence (AI) on employee performance in the economic industry. Digital literacy encompasses the ability to understand, use, and manage digital information effectively, which is a crucial element in supporting digital transformation in the workplace. Meanwhile, AI offers various opportunities to enhance productivity, efficiency, and innovation in company operations. This research employs a quantitative approach using a survey method to collect data from employees working in various sectors of the economic industry. The findings indicate that digital literacy proficiency has a significant positive correlation with employees' ability to utilize AI technology. Employees with high digital literacy are more likely to understand and optimally use AI applications to support their tasks. Furthermore, effective AI utilization has been proven to contribute to improving employee performance, particularly in aspects such as efficiency, work quality, and adaptability to new challenges. The combination of strong digital literacy and strategic AI utilization significantly impacts an organization’s success in facing competition in the digital economy era. This study emphasizes the importance of digital literacy training programs and the integrated implementation of AI technology to enhance employee competencies as part of human resource development strategies.